Filmes de 'CO' obtidos por deslocamento galvânico e suas propriedades magnéticas - Sakita, Alan Massayuki Perdizio [UNESP] (2014)
This work comprises the cobalt deposition onto zinc by using the galvanic displacement technique. The cobalt films were prepared from chloride and sulfate baths with and without glycine, and at pH 3 and 5. The deposits were characterized by: SEM, OM, EDXS, XRD and VSM. During the deposition process, it was monitored the open circuit potential and subsequently were conducted electrochemical impedance spectroscopy (EIS) measurements in order to elucidate the possible processes that may occur during the galvanic deposition. The results showed that the glycine addition leads to a more homogeneous deposition and no byproducts, such as Zn5(OH)8Cl2.2H2O and Zn4(SO4)(OH)6.4H2O, are formed. Furthermore, the glycine addition to the bath revealed a higher hydrogen evolution during the deposition process, possibly related to the deprotonation of glycinate ion. The electrochemical study of the galvanic displacement process by measuring the open circuit potential revealed a higher potential stability when glycine was employed in the bath. The monitoring of cobalt deposition by EIS showed that the Co2+ ions facilitate the process of Zn dissolution. By increasing the glycine concentration and the deposition time, the capacitance values, related to the double electric layer, increase and the charge transfer resistance decreases, suggesting that both parameters induce an increase in the electrode area. The magnetic properties of the Co deposits, extracted from the VSM measurements, exhibited the highest saturation magnetization for the deposit obtained from chloride bath at pH 3 without the glycine addition, indicating the presence of a higher amount of metallic Co in this condition. In the case of the sulfate bath, the highest saturation magnetization was reached for the deposits obtained at pH 5 in the presence of glycine.